Klavierschule - Türk, Daniel Gottlob 1750-1813; Jacobi, Erwin R. 1909-1979 (Kassel Bärenreiter, 1967)
Faksimile-Nachdruck der 1. Ausgabe 1789.
Keywords: 18th Century (1701-1800); Method; Keyboard instrument; Germany